Pendampingan Penyusunan Standard Operating Procedures (SOP) Sekretariat DPRD - Siti Rofingatun (UNIVERSITAS CENDERAWASIH, 2018)
The advisory activities for the preparation of standard operating procedures (SOP) is a community service activity that aims to produce a draft of SOP for the secretariat of the council as well as enhancement of understanding related to the theory, principles, and techniques of SOP preparation for SETWAN in accordance with government regulation. The participants of this activity are 65 people that actively participated in the event for three working days.